Pengaruh Kepemimpinan Partisipatif Pada Kinerja Mahasiswa Magang: Peran Mediasi Kepercayaan Pada Organisasi - Supeno; Ali Audah (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2019)
Research involving final-year students’ university internship on Islamic High School for three months. Students completing measure instruments that developed by researcher. Data covered used to test of direct and indirect effect of participative leadership toward task and contextual performance with mediation of affective and cognitive-trust in leader. Result of analysis shows participative leadership, affective and cognitive-trust in leader simultaneously has positive influence toward task and contextual performance. Participative leadership partially has positive influence on both task and contextual performance as well as on affective and cognitive-trust in leader. Affective-trust in leader partially has positive influence on task performance. Direct effect of participative leadership on task performance was bigger from indirect effect by affective-trust in leader, and total effect was bigger from direct effect. Influence of participative leadership on task performance unmediated by affective-trust in leader. Because contextual performance uninfluenced by affective-trust in leader, so affective-trust unmediated for influence of participative leadership on contextual performance. Because no influence of cognitive-trust on task and contextual performance, so cognitive-trust unmediated for influence of participative leadership, both on task or contextual performance. Research finding would discuss in students internship context.